Pengembangan Bahan Ajar Mata Pelajaran Pendidikan Agama Islam oleh Guru Tingkat Sekolah Dasar - Nyairah, Nyairah (Social Science Academic, 2024)
2013 curriculum emerged as an effort from the previous curriculum development in order to realize interactive, effective, and certainly more productive learning. Various advantages were obtained by teachers from this curriculum, including the teacher could be more flexible in developing teaching materials so that students can develop optimally. The research here specifically discusses the development of Islamic Religious Education teaching materials by teachers at 1 Babadan Balerejo Elementary School, Madiun. The formulation of the problem was regarding the objective conditions of Islamic Religious Education teaching materials, the problems faced by the teachers in developing teaching materials and finally the steps taken by Islamic Religious Education teachers to develop teaching materials at 1 Babadan Balerejo Elementary School, Madiun. The approach used in this research was qualitative with the type of case study. The results obtained are the objective conditions of teaching materials in accordance with the 2013 Curriculum, the teacher is responsible for preparing learning implementation plans while the Islamic Religious Education subject matter that has been determined is developed by the teacher himself. The problems faced by teachers are the determination of teaching materials that are relevant to competency standards and basic competencies, lack of infrastructure and problems that arise from students who do not understand the material coupled with limited sources of teaching materials. The steps in developing teaching materials are relevant to the standard process, the teacher has selected teaching materials in accordance with competency standards, used varied strategies, and implemented learning evaluations in accordance with the 2013 curriculum.